« Penser base-ball » - Peter Marquis (Association Française d'Etudes Américaines, 2012)
Around 1900, large American cities saw the rise of charity organizations that instrumentalized sports to revitalize the nation. An outgrowth of various intellectual movements, the sportization of voluntary organizations directly affected Brooklyn and “its” Dodgers. From the opening of Ebbets Field in 1913, but especially from 1943 during the presidency of Branch Rickey, the Dodgers front-office cultivated strong ties with the borough’s charities via its own Brooklyn Amateur Baseball Foundation. The organizations it supervised lauded baseball for its physical benefits but especially for the socialization it provided in these worried times. Being “baseball-minded” meant much more than focusing on the intricacies of the game. A weapon against “juvenile delinquency” and communism, baseball was thought to shape the minds of future citizens and to convey the values the country embraced in its post-1945 reconstruction years. This belief, shared by a small group of Brooklyn youth experts, reflected and shaped attitudes and representations, especially regarding young African-Americans, the first to be passed over in the club’s charity work.